Rapid detection of human cytomegalovirus by multienzyme isothermal rapid amplification and lateral flow dipsticks - Liu, Ming-hui; Guo, Xiaochong; Sun, Mao-ling; Li, Jia-lun; Liu, Shu-han; Chen, Yun-zhou; Wang, Dong-yi; Wang, Lan; Li, Yu-zhang (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionHuman cytomegalovirus (HCMV) is the most common viral infection seen in newborns. The major route of transmission for acquired human cytomegalovirus infection is breast milk from mothers who are HCMV seropositive to the infants. Thus, a rapid, economical, and simple method to perform HCMV test in breast milk is crucial and necessary for preventing acquired HCMV infection, especially in underdeveloped regions with limited laboratory resources.MethodsIn this study, an effective technique for the detection of HCMV was constructed by combining multienzyme isothermal rapid amplification (MIRA) and lateral flow chromatography strip (LFD). Primers for the conserved HCMV sequence UL83 were utilized for MIRA-LFD testing.ResultsOur results showed that the entire MIRA reaction could be completed in 12 minutes at 37°C, and LFD outcomes could be observed visibly after 10 minutes. The detection sensitivity of this method reached 50 copy/μl. Samples of breast milk were examined to compare MIRA-LFD and conventional qPCR. The accuracy of MIRA-LFD was 100%.DiscussionThe straightforward, rapid, economic features of the test can provide the significant advantages for the prevention of breast milk-acquired cytomegalovirus infection, particularly in resource-limited locations with high seroprevalence of cytomegalovirus.